2008
DOI: 10.1111/j.1533-8525.2008.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Race and The Educational Expectations of Parents and Children: The Case of South Africa

Abstract: South Africa, a country that is highly stratified by race, is an important location for studying the relationship between race and educational expectations. Using a longitudinal data set, we examine the educational expectations of black (African), colored (mixed race), and white (European ancestry) parents and children in Cape Town, South Africa. We find that parents and children have high educational expectations regardless of race, but black parents and children have higher educational expectations than colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…This motivational function of parental expectations is supported by eight articles demonstrating a strong association between parental expectations and students' expectations or aspirations (Benner and Mistry 2007;Beutel and Anderson 2008;Carpenter 2008;Hao and Bonstead-Burns 1998;Rutchick et al 2009;Smith-Maddox 2000;Trusty 2002;Trusty et al 2003). A recent longitudinal study of 884 children aged 6 to 13 years when the study began demonstrated the long-lasting effect of parental expectations on children's expectations.…”
Section: High Parental Expectations Indicate That Parents Value Achiementioning
confidence: 76%
See 3 more Smart Citations
“…This motivational function of parental expectations is supported by eight articles demonstrating a strong association between parental expectations and students' expectations or aspirations (Benner and Mistry 2007;Beutel and Anderson 2008;Carpenter 2008;Hao and Bonstead-Burns 1998;Rutchick et al 2009;Smith-Maddox 2000;Trusty 2002;Trusty et al 2003). A recent longitudinal study of 884 children aged 6 to 13 years when the study began demonstrated the long-lasting effect of parental expectations on children's expectations.…”
Section: High Parental Expectations Indicate That Parents Value Achiementioning
confidence: 76%
“…Carpenter (2008) noted that correlations between parental expectations and expectations of 10th to 12th graders were weaker for Latino students with an immigrant parent compared with nonLatino students with an immigrant parents. Beutel and Anderson (2008) found that South African parents' expectations when their children were in the 8th grade was a significant predictor of students' educational expectations at 11th grade for Asian and mixed race students but not for Blacks after controlling for parents' education, previous literacy/numeracy scores, and whether or not the student was enrolled in school at the time of 11th grade. What may account for this pattern of weaker relations between parental and student expectations for racial/ethnic minorities than for European American families?…”
Section: High Parental Expectations Indicate That Parents Value Achiementioning
confidence: 97%
See 2 more Smart Citations
“…Results also show that parents' expectations are tied to the local village cultural environment. However, among the large number of studies of parents' and children's educational expectations, only a few explore the influence of parent-child agreement and disagreement in expectations on children's schooling (Furstenberg 1971;Smith 1981 Smith , 1982 Smith , 1991Hao and Bonstead-Bruns 1998;Kim and Schneider 2005;Beutel and Anderson 2008). To date, there are almost no studies that examine longitudinally the reciprocal influence between parents and children in their educational expectations, and the associations of early expectations and children's later educational outcomes.…”
mentioning
confidence: 99%